Design and Development of a Web-Based System using Laravel Framework: A Competition Management System - Zafri Azran, Nur Zahira Afiqah; Wahid, Norfaradilla (Applied Information Technology And Computer Science, 2022)
Competition is a common activity that has been held among the community. It is the event that requires gathering of the people who join. It can be inconvenient when the venue is far from the participant's place. This activity is also obstructed due to this covid era. Participants do not have access for the data and history of the competitions as they are only kept by the administrator. Therefore, a web-based competition management system is proposed to let people organize and participate in competition virtually. In addition, people can create and join many competitions at a time. Through the system, judges can directly evaluate the submissions. The system is developed according to the Agile Scrum Methodology. This system is developed using the PHP Framework, Laravel and MariaDB database. At the end of project development, testing phase has shown that the system is successfully met all the requirements in terms of the functionality. Each module has been implemented according to the business plan diagram. This system is expected to ease the online management of competition and bring people forward to the digitalization community.